Prediction of subclinical atherosclerosis in low Framingham risk score individuals by using the metabolic syndrome criteria and insulin sensitivity index - Huang, Benjamin; Huang, Weiting; Allen, John Carson; Sun, Lijuan; Goh, Hui Jen; Kong, Siew Ching; Lee, Dewaine; Ding, Cherlyn; Bosco, Nabil; Egli, Leonie; Actis-Goretta, Lucas; Magkos, Faidon; et al. (Frontiers in Nutrition, 2022)
Background: Subclinical atherosclerosis can be present in individuals with an optimal cardiovascular risk factor profile. Traditional risk scores such as the Framingham risk score do not adequately capture risk stratification in low-risk individuals. The aim of this study was to determine if markers of metabolic syndrome and insulin resistance can better stratify low-risk individuals. Methods: A cross-sectional study of 101 healthy participants with a low Framingham risk score and no prior morbidities was performed to assess prevalence of subclinical atherosclerosis using computed tomography (CT) and ultrasound. Participants were compared between groups based on Metabolic Syndrome (MetS) and Insulin-Sensitivity Index (ISI-cal) scores. Results: Twenty three individuals (23%) had subclinical atherosclerosis with elevated CT Agatston score ≥1. Presence of both insulin resistance (ISI-cal <9.23) and fulfilment of at least one metabolic syndrome criterion denoted high risk, resulting in significantly improved AUC (0.706 95%CI 0.588-0.822) over the Framingham risk score in predicting elevated CT Agatston score ≥1, with net reclassification index of 50.9±23.7%. High-risk patients by the new classification also exhibited significantly increased carotid intima thickness. Conclusions: The overlap of insulin resistance and presence of ≥1 criterion for metabolic syndrome may play an instrumental role in identifying traditionally low-risk individuals predisposed to future risk of atherosclerosis and its sequelae.